2004
DOI: 10.1093/bja/aeh033
|View full text |Cite
|
Sign up to set email alerts
|

Relation between fentanyl dose and predicted EC 50 of propofol for laryngeal mask insertion

Abstract: A fentanyl dose of 0.5 micro g kg(-1) is sufficient to decrease predicted EC(50LMA) with minimum respiratory depression and without a high BIS value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 13 publications
5
31
0
Order By: Relevance
“…Furthermore, Kodaka et al [16] reported that fentanyl pretreatment reduced the 50% effective concentration of propofol for cLMA insertion, but propofol requirements did not differ whether 1 or 2 lg.kg )1 of fentanyl was given. Goyagi et al [17] have also shown the effect of fentanyl on propofol requirement for cLMA insertion, where fentanyl 2 lg.kg )1 reduced the propofol requirement by 60%, but at the expense of prolonged respiratory depression. These studies are in concordance with our findings.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Kodaka et al [16] reported that fentanyl pretreatment reduced the 50% effective concentration of propofol for cLMA insertion, but propofol requirements did not differ whether 1 or 2 lg.kg )1 of fentanyl was given. Goyagi et al [17] have also shown the effect of fentanyl on propofol requirement for cLMA insertion, where fentanyl 2 lg.kg )1 reduced the propofol requirement by 60%, but at the expense of prolonged respiratory depression. These studies are in concordance with our findings.…”
Section: Discussionmentioning
confidence: 94%
“…The properties of rapid onset and offset of action and of smooth recovery (6) make propofol an appealing agent alone or in combination with an opioid for procedural sedation (7)(8)(9)(10). However, dose-dependent respiratory depression and hypoxemia are possible, owing to interactions and synergism between sedatives and opioids (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Fentanyl 0.5, 1, and 2 μg·kg −1 combined with propofol decreased the EC 50 of propofol for CLMA insertion [4]. The authors of that study concluded that supplemental 0.5 μg·kg −1 fentanyl was suffi cient to decrease the predicted EC 50 with minimal respiratory depression.…”
Section: Introductionmentioning
confidence: 98%